The Relationship Between Green Space and Prosocial Behaviour Among Children and Adolescents: A Systematic Review - Putra, I Gusti Ngurah Edi; Astell-Burt, Thomas; Cliff, Dylan P.; Vella, Stewart A.; John, Eme Eseme; Feng, Xiaoqi (Frontiers in Psychology, 2020)
The plausible role of nearby green space in influencing prosocial behaviour among children and adolescents has been studied recently. However, no review has been conducted of the evidence testing the association between green space and prosocial behaviour. This systematic review addresses this gap among children and adolescents. Within this review, we proposed a conceptual framework describing potential pathways linking green space to prosocial behaviour, discussed the direction, magnitude, moderators, and mediators of the association, and developed a narrative synthesis of future study directions. Out of 63 extracted associations from 15 studies, 44 were in the positive or expected direction, of which 18 were reported to be statistically significant (p<0.05). Overall, the current evidence shows that exposure to green space may potentially increase prosocial behaviour among children and adolescents, with some contingencies (e.g. child’s sex, ethnic background). However, the volume and quality of this evidence is not yet sufficient to draw conclusions on causality. Further, heterogeneity in the indicators of green space exposure could lead to mixed findings. In addition, none of the included studies investigated potential mediators. Nevertheless, this review provides preliminary evidence and a basis for further investigation with rigorous study methodology capable of drawing causal inferences and testing potential effect modifiers, linking pathways, and relevant green space measures.